PREPARATION OF NANO SILICA FROM SILICA SAND THROUGH ALKALI FUSION PROCESS - Agus Wahyudi; Dessy Amalia; Sariman Sariman (Indonesian Mining Journal, 2013)
Silica (SiO2) materials play an important role for industries, especially those in micron or even nano-scale size. The later has better properties and improves its quality. Nano silica is applied widely in building material, notably as a mixture of concrete. The material is also promising to be developed into amorphous nano silicon for solar cell materials. Indonesia has a lot of silica sand resources and faces a challenge to increase its quality into high product such as nano silica. Synthesizing silica nano through alkali fusion is a process that includes using the particles along with sodium hydroxide at temperature of 400-1100 °C then recrystalizing the molecules to get materials in nano size. The recrystalizing process was conducted by water leaching and filtration. The derived nano particles (gel) ranged between 40-60 nm. TEM characterization showed that the products are homoge- neous, well dispersed and has specific surface area around 157 m2/g.